Cutaneous and subcutaneous Kaposi's sarcoma lesions treated with electrochemotherapy. (12th May 2022) - Lalanda, Raquel; Bartolo, Joana; Carvalhal, Sara; Abecasis, Nuno; Farricha, Victor
Abstract: Background and Objectives: Kaposi's sarcoma (KS) is a locally aggressive mesenchymal tumor that involves the lymphovascular system, with a tendency to become multifocal. Electrochemotherapy (ECT) is considered a valuable treatment option in selected patients with cutaneous and subcutaneous KS lesions. Methods: We report a retrospective study that included 14 classic and endemic KS patients that underwent ECT sessions for the treatment of KS cutaneous and subcutaneous lesions at our institution. Results: According to Response Evaluation Criteria in Solid Tumors (RECIST) version 1.1 criteria, our patients had an overall response rate (ORR) of 100% to the ECT treatment. A complete response (CR) was obtained in 92.8% of patients after one or more ECT sessions. Only one patient had a progressive disease (PD). The treatment was well tolerated with a low complication rate, mainly transitory local pain or skin ulceration. Conclusions: ECT represents a locoregional therapy for containment and symptomatic control of classic and endemic KS cutaneous and subcutaneous lesions. Further studies including different subtypes of KS patients should also be performed.